Caracterização da ictiofauna durante o período seco, na Baía do Guajará e Baía do Marajó - MELO, Ylana Priscila da Costa (Universidade Federal do Pará, 2013)
The Bay of Guajará and Bay of Marajó coverage area of search and inserted into the context of the estuary Paraense, are characterized by receiving the majority of freshwater discharge and submit macrotidal area. The fishing in this region is of great importance to the economy of several municipalities in the state of Pará, including the capture of several species and different fishing gear and two fleets and technologically distinct (artisanal and industrial). As part of the research study in the Bay of Guajará and Bay of Marajó, it was necessary to contribute with important information related to biology and ecology of the environment, where such information was used to perform the characterization of the fish fauna of the area during the dry period in order to survey the local diversity, since the majority of fish landed in Bethlehem is from these areas through fishing. The study included areas belonging to the state of Pará, covering the port terminals Bay of Guajará and Bay of Marajó. An extra collection was performed in the area of the island of Mosqueiro. The data available so far do not show differentiation in the composition of the fauna of the areas studied. It was estimated a total of 37 fish species, accounting for 4379 individuals in the Bay of Guajará Bay of Marajó and Mosqueiro island, where the family was more representative Scianidade grouping species that contributed the most, which were: Hake (Plagioscion squamosissimus) and Curuca (Stellifer rastrifer) (assumed to be constant, ie, effectively making up the fish fauna of the place in the bay of Guajará, as in the bay of Marajó and the island of Mosqueiro). Among the 37 species, 4 were considered constant, 26 were occasional white and 7 catches. Hake (Plagioscion squamossisimus) and Curuca (Stellifer microps) were the most important species for fisheries in terms of catch per unit effort (CPUE), frequency of occurrence, and relative contribution of Simper analysis (multivariate). Being only the island of Mosqueiro that stood out: Mackerel (Pellona flavipinis), because of marine influence in this area is higher, which thus characterizes the local biota and distinguish it from other regions. Overall diversity was low with greater variations, and the evenness remained free of major difference between the areas. The area had low species diversity compared to other estuaries, mainly explained by the high hydrodynamic of the area and high flow vessels, making the environment inhospitable to the emergence of some species. More emphasis has earned the bay of Guajará has great ecological importance because it is considered as the nursery, and therefore economical, as there are commercial species that spend part of their life cycle there.